INTEGRASI KONSELING ISLAM DALAM PENGUATAN SELF-AWARENESS UNTUK MEWUJUDKAN KEHARMONISAN KELUARGA - Andany Danty Susanto; Keti Yuliantika (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2025)
Self-awareness is the primary foundation for building family harmony. Amidst the currents of modernization, rife with social pressures, the influence of digital media, and shifting moral values, many individuals struggle to identify themselves, understand their emotions, and balance them within the family. The method used was a descriptive qualitative literature study, which examined various theories and previous research findings related to the topic. The study's findings indicate that Islamic counseling plays a significant role in fostering self-awareness through a process of spiritual reflection, emotional management, and continuous self-evaluation (muhasabah). Individuals with a high level of self-awareness tend to be better able to understand their strengths and weaknesses, manage psychological stress, and foster empathy for other family members. This contributes to healthy communication, mutual respect, and harmonious relationships within the family. Therefore, Islamic counseling serves not only as a means of psychological healing but also as a comprehensive mental and spiritual training medium. Through Islamic values ​​such as sincerity, patience, and responsibility, this counseling contributes to fostering self-balance and creating a family that is peaceful, loving, and compassionate.   Keywords: Islamic counseling, self awareness, family harmony.